Governing the Sustainable Development Goals Quantification in Global Public Policy - Bandola-Gill, Justyna (Sustainable Development Goals Series, 2022)
This open access book conceptualises the Sustainable Development Goals as epistemic infrastructures that connect numbers, networks and governing paradigms.The book approaches quantification not merely as a tool for governing, but rather as a broader epistemic system through which global public policy is produced. This book focuses on the role of international organisations in shaping and implementing the 2030 Agenda and demonstrates how the SDGs have transformed and accelerated trends in quantification.